A methodological assessment of randomization integrity in alteplase for acute ischemic stroke individual patient data meta-analyses. - Ravi Garg; Gabriel Torrealba-Acosta; Steffen Mickenautsch; Vance W Berger (PLoS ONE)
Objectives Little is known about the integrity of randomization for randomized controlled trials (RCT) included in alteplase for stroke meta-analyses. If the RCTs were not properly randomized, the results could not be accepted at face value. The objective was to assess the integrity of randomization in individual patient data (IPD) meta-analyses supporting alteplase for acute ischemic stroke. Methods We assessed randomization reporting, performed qualitative risk of bias assessments arising from the randomization process, and performed fixed effects meta-analyses of baseline variables for which zero heterogeneity is expected if all included RCTs have unbiased randomization. Fixed-effects meta-analyses of baseline age, weight, and National Institute of Health Stroke Scale (NIHSS) score were performed. If heterogeneity was present (I2 >  0%), trials were systematically removed, starting with the RCT with the largest t-statistic until the I2 value was 0%. Results The NINDS rt-PA Stroke Study had a high risk of bias, the ECASS-3 RCT had some concerns, and all other trials were graded as low risk according to the Cochrane Risk of Bias (ROB-2) tool. The NINDS rt-PA Stroke Study contributed to heterogeneity in age and weight meta-analyses, and the ECASS-3 RCT contributed to heterogeneity in the NIHSS score meta-analysis. Removal of suspect trials resulted in the expected I2 value of 0%. Conclusions The NINDS rt-PA Stroke Study and ECASS-3 trials contributed to heterogeneity in fixed effects meta-analyses of baseline variables while there should have been none. These RCTs are likely a source of selection bias in IPD meta-analyses due to suspect randomization.